Phase I study of sorafenib in combination with everolimus (RAD001) in patients with advanced neuroendocrine tumors - Chan, Jennifer A. (2013)
PURPOSE: Sorafenib and everolimus are both active against neuroendocrine tumors (NET). Because of potential synergy between VEGF pathway and mTOR inhibitors, we performed a phase I study to evaluate the safety and feasibility of combining sorafenib and everolimus in patients with advanced NET. METHODS: Patients were treated with everolimus 10 mg daily in combination with sorafenib (dose level 1: 200 mg twice daily; dose level 2: 200 mg per morning, 400 mg per evening) using standard phase I dose escalation design. Dose-limiting toxicity (DLT) was defined within the first cycle (28 days) of therapy. Treatment was continued until tumor progression, unacceptable toxicity, or withdrawal of consent. Twelve additional patients were treated at the maximum tolerated dose (MTD) level to further characterize safety and a preliminary assessment of activity. RESULTS: One patient in Cohort 1 experienced DLT (grade 3 skin rash); the cohort was expanded to 6 patients with no further DLTs. All 3 patients in Cohort 2 experienced DLT, consisting of thrombocytopenia, hand–foot skin reaction, and rash/allergic reaction. Sorafenib 200 mg twice daily in combination with everolimus 10 mg daily was established as the MTD. Independently reviewed best objective responses revealed that 62 % of patients had some degree of tumor shrinkage. By RECIST, we observed partial response in 1 patient, stable disease in 13 patients, and progressive disease in 3 patients. CONCLUSION: Sorafenib 200 mg twice daily with everolimus 10 mg daily represents the MTD of this combination in patients with advanced NET. While the combination is active, toxicity concerns may preclude more widespread use.